Effectiveness of different curing media in self-healing process monitored by compressive strength and water absorption of cement mortar - Mokhtar, Norfaniza; Wan Jusoh, Wan Amizah; Mah Hassan, Muhammad Fitri (Springer, 2020)
The root cause of the majority of structural failure is attributed to cracking, there is a compelling economic incentive to develop concrete that can treat and repair the damage by itself. Even though some research has been carried out in this area a breakthrough in method to supply nutrient for effective healing are yet to materialise. For the present study, Bacillus sphaericus with diatomaceous earth as a protective vehicle was selected to determine the best performance with different curing media as an alternative method to supply a nutrient. For the growth of the bacterial, the nutrients are supplied using three different curing media which is deposition medium (controlled nutrients), runoff water (uncontrolled nutrients) and also distilled water. The performance of Bio-based cement mortar (BBCM) was evaluated by comparing the influence on compressive strength and water absorption subjected to different curing media. BBCM cured in run-off water had the best compressive strength with increment of 39.04% compared to others curing media. Also, with its great dispersal characteristics, denser BBCM with a reduction of water absorption. BBCM cured in run-off water had a 40% improvement in strength compared to normal curing. As a conclusion, run-off water is highly promising in supplying sufficient nutrients to bacteria for the biomineralization process to pro- duce CaCO3. This work also aims to apply this approach in the field especially in sewerage and drainage system.